Pendampingan Pembuatan Konten Youtube Bagi Siswa SMA At Thohiriyyah Semarang - astuti, yani parti; Subhiyakto, Egia Rosi; Dolphina, Erlin; Sutojo, Totok; Rafrastara, Fauzi Adi; Kartikadarma, Etika (LPPM UNIVERSITAS DIAN NUSWANTORO, 2024)
The extraordinary use of YouTube at this time indicates that developments in the world of technology are very rapid. But it must always be aware that technological developments also affect the psychological development of children. As is the case at the age of children - teenagers who sometimes cannot control. The development of the use of technology, information and communication in the digital world has had various impacts on our lives. As happened at SMA At Thohiriyyah Semarang, which has a middle to lower economic background and is located on the outskirts of East Semarang. At that high school, the students still don't understand the correct use of YouTube. They just watch content that is sometimes not useful. With these problems, they must be given assistance on how to use YouTube properly. For this reason, they must be made active in using YouTube by having an account and being able to create useful content for other people. Apart from that, they are expected to be able to entertain other people through the content they create